A Look At Grit: A Study towards Malaysian Technical Instructor’s Performance Retention - IBRAHIM, BADARUDDIN BIN; MOHAMAD, NURUL HAERANI BINTI; AZIZ , AZLIHAN BIN ABD; KADIR , MAHADI BIN; HAMID, ZULISHAM BIN ABD (International Journal of Psychosocial Rehabilitation, 2020)
The improvement of instructors’ professionalism and quality should be prioritized to achieve Malaysia’s Education Blueprint 2013-2025 goals. Most of previous studies suggested that, teachers’ effectiveness and performance retention could be measured by the impact of instructors on students’ achievement, but none of the study measure t instructors’ effectiveness and performance retention through grit. Grit can be an important factor in explaining the achievement and persistence in maintaining the expected quality of t instructors’ performance. This study investigated Malaysian Technical Instructors and the grit needed to stay in the field especially in purifying the state’s aspirations. The purpose of this study was to describe grittiness of technical instructors and determine if grit is associated with job performance retention based on age, education level and years of services. The data for this research was obtained through structured questionnaire adapted from Grit-S survey and involved 88 technical instructors from Malaysia Technical Institute under Rural Development Ministry of Malaysia. The study findings identified that grit: the power of passion and perseverance not associated for long lasting job performance retention among Malaysian Technical Instructors. More broadly, this study provides a qualitative and dimensional understanding of the phenomena of grit as related to job performance retention.